Puzzle Gizi sebagai Upaya Promosi terhadap Perilaku Gizi Seimbang pada Siswa - Ade Saputra Nasution; Andreanda Nasution (Media Kesehatan Masyarakat Indonesia, 2020)
Health education, especially nutrition needs to be done for children from an early age such as elementary school students. This is an effort to create awareness of balanced nutrition behavior in everyday life. One way of health education that needs to be done by students is to use educational media such as nutritional puzzles. This study aims to analyze differences in behavior (knowledge, attitudes, and actions) before and after the intervention using a nutrition puzzle. This study uses a Pre Experimental design One Group Pre-test Post-test design with a sample of 53 respondents obtained by sampling that is proportional stratified random sampling, and data analyzed using the McNemar test. The results of the study describe the characteristics of 19 men and 34 students from women, data analysis illustrates knowledge (p = 0.001), attitude (p = 0,000) and action (p = 0,000) which means knowledge, attitude and actions have differences before and after given an intervention using a nutrition puzzle. There should be a way of balanced nutrition promotion among elementary school students who support changes in behavior (knowledge, attitudes and actions) of students towards healthier lifestyles.